FINANCIAL RATIO AND COMPANY VALUE IN COMPANIES BEFORE AND AFTER CONDUCTING AN INITIAL PUBLIC OFFERING (IPO) IN 2019-2020 - Ambenur, Putra Agustri; Dantas, Rui Miguel (International Journal of Contemporary Accounting, 2024)
This study is motivated by a significant increase in companies conducting Initial Public Offerings (IPO) in 2023. This increase is the largest in the Indonesian Stock Exchange (IDX) history since 1990. This study aims to obtain empirical evidence about the differences in company financial performance before and after conducting an IPO in 2019-2020 with 412 samples used in this study. Secondary data is applied in this study with the Wilcoxon Sign Rank Test to compare analysis of the difference. This study’s result show significant difference in the company’s Current Ratio, Debt to Equity Ratio, Return on Equity Ratio, and Total Asset Turnover Ratio before and after conducting IPO. The results of this study also represent that there is no significant difference in the company's Net Profit Margin, and Tobin's Q before and after the IPO. This study contributes to our understanding of how IPO impacts a company's financial performance. This study provides insight into how appropriate business and investment decisions can be determined. Furthermore, this study also contributes especially to investors to carefully analyze the financial performance and value of companies for decision making. This study is unique due to variations from previous studies in terms of observation time, location, population, sample, and measurement methods, as it incorporates Tobin's Q measurement to assess firm value. This study can strengthen existing theories by providing additional evidence from different contexts or populations.